2005
DOI: 10.1080/00150190500318644
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Boron Addition on the Dielectric Properties of Giant Dielectric CaCu3Ti4O12

Abstract: The recently discovered giant dielectric CaCu 3 Ti 4 O 12 (CCTO)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…The dielectric loss increases without any peak at high frequency. This is a signature of stray inductance of the contacts and leads [4]. Incidentally, increasing the P 2 O 5 concentration beyond 1% deteriorates the dielectric properties of the material (k value for 3% and 5% P 2 O 5 incorporated samples are 870 and 470 at 1 kHz, respectively) which is in agreement with the decreasing trend of bulk density with P 2 O 5 content.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…The dielectric loss increases without any peak at high frequency. This is a signature of stray inductance of the contacts and leads [4]. Incidentally, increasing the P 2 O 5 concentration beyond 1% deteriorates the dielectric properties of the material (k value for 3% and 5% P 2 O 5 incorporated samples are 870 and 470 at 1 kHz, respectively) which is in agreement with the decreasing trend of bulk density with P 2 O 5 content.…”
Section: Resultssupporting
confidence: 78%
“…2 represents the variation of bulk density of CCTO with P 2 O 5 addition after sintering at 1000 8C for 40 h. It can be seen that the density is maximum for 1% P 2 O 5 incorporated sample and the density increases with soaking time. It is expected that P 2 O 5 forms a glassy phase [4] and helps in liquid phase sintering of CCTO. For liquid phase sintering there is an optimum amount of liquid phase [11] above which the densification decreases as has been found in the present case.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although, CCTO possesses giant dielectric constant, the dielectric losses are too high to commercialize it. Number of attempts has been made to decease tan ı by various compositional modifications such as Cr 2 O 3 -doped CCTO [7], ZrO 2 -doped CCTO [8], CCTO/CaTiO 3 composite [9], B 2 O 3 doped CCTO [10], TiO 2 -rich CCTO [11,12] and La substitution on Cu sites in CCTO [13] have been reported to be effective in reducing the dielectric loss and still maintaining high dielectric constant. In a study by Cheng et al [14], it was shown that in La doped CaCu 3 Ti 4 O 12 , Ca site is completely substituted by La without influencing the phase transition.…”
Section: Introductionmentioning
confidence: 98%